Modern economist as a professional linguistic personality: success and challenges of formation in Higher Economics School (Pedagogy of Higher and Secondary Education, 2013)
Semenog O. N., Semenog A. Y. Modern economist as a professional linguistic personality: success and challenges of formation in Higher Economics School.The report is devoted to the certain aspects of language, terminology, communicative, textual, discursive competence of the person skilled in economic sphere. The presentation describes the influence of the individual of economist on the formation of the linguistic identity of the student - the future economist.
Keywords: economist; professional linguistic text; linguistic personality; the language; terminology; communicative; textual; discursive competence